2015
DOI: 10.1016/j.alcohol.2014.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock genes: Effects on dopamine, reward and addiction

Abstract: Addiction is a widespread public health issue with social and economic ramifications. Substance abuse disorders are often accompanied by disruptions in circadian rhythms including sleep/wake cycles, which can exacerbate symptoms of addiction and dependence. Additionally, genetic disturbance of circadian molecular mechanisms can predispose some individuals to substance abuse disorders. In this review, we will discuss how circadian genes can regulate midbrain dopaminergic activity and subsequently, drug intake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 110 publications
(123 reference statements)
1
100
0
Order By: Relevance
“…Twenty-four papers were not specifically included: 20 related to methylphenidate rather than ethylphenidate, 3 described ethylphenidate's use as an internal standard for measuring methylphenidate, and a further paper related to analytical identification of ethylphenidate [6,7,9,10,[12][13][14][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four papers were not specifically included: 20 related to methylphenidate rather than ethylphenidate, 3 described ethylphenidate's use as an internal standard for measuring methylphenidate, and a further paper related to analytical identification of ethylphenidate [6,7,9,10,[12][13][14][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Resultsmentioning
confidence: 99%
“…It is an analogue of methylphenidate that has significantly greater dopaminergic selectivity, with a 16-fold greater affinity for the dopamine transporter than the noradrenaline transporter, as compared with methylphenidate [6]. This potentially increases the addiction potential of ethylphenidate [7].…”
Section: Introductionmentioning
confidence: 98%
“…Dopamine is a highly expressed neurotransmitter that is involved in the regulation of diverse biological effects including reward, locomotor activity, cognition, hormone secretion, food intake and circadian rhythms [33,34]. Effects of dopamine are elicited via a family of G-protein coupled dopamine receptors (D1–5) which are expressed throughout the body (including in bone) and signal via distinct pathways [35].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, nocturnal hyperactivity, as well as anxiety and depression, may contribute to poorer sleep in patients with ICDs. Also, it has been suggested that behavioural addiction in itself may influence sleep–wake cycle regulation by modulating the expression of the so-called clock genes 30. On the other hand, sleep deprivation may increase impulsivity and enhance emotional reactivity via a dysfunction of the prefrontal cortex–amygdala interactions 31 32.…”
Section: Discussionmentioning
confidence: 99%